Gaze And Shoot: Examining the Effects of Player Height and Attacker-Defender Interpersonal Distances on Gaze Behavior and Shooting Accuracy of Elite Basketball Players - Pedro T. Esteves; Jorge Arede; Bruno Travassos; Matt Dicks, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
The current study seeks to investigate the effects of player height and attacker-defender interpersonal distances on gaze behaviour and shooting performance of elite basketball players. To this end, ten male professional basketball players were evaluated during a shooting task involving five experimental conditions: defender positioned at 0.5m, 1m, 1.5m and 2m of distance to the attacker and an additional control condition with no defender. A wireless SMI eye-tracking glasses system was worn by each attacker for the purpose of monitoring their gaze behaviour in view of the experimental conditions. Shot efficacy and attackers’ height was also evaluated. Results indicate an effect of the presence of the opponent and their body height on gaze behaviour when attempting to shoot at the basket. A greater number of fixations was found on the body of the defender, and less on the rim, for close interpersonal distances between the shooting attacker and the immediate defender (0.5m). No differences were found in fixation duration. It was also found that attackers with greater body height exhibited superior shot efficacy than those with smaller body height. In conclusion, these results suggest that when aiming at the scoring target in basketball, both performance and gaze behaviours of the attackers are sensitive to the impending constraints related to the presence of the opponent as well as to their own body size properties. Accordingly, the design of representative shooting tasks in basketball should consider the manipulation of individual and task constraints such as the interpersonal distance between shooting attacker and immediate opponent as well as body height differential.